PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DENGAN STRATEGI PROBLEM POSING UNTUK MELATIHKAN KETERAMPILAN BERPIKIR KREATIF PESERTA DIDIK PADA MATERI REAKSI REDOKS - Jannah, Roudlotul; Rusmini, Rusmini (Universitas Negeri Semarang, 2020)
Creative thinking skills are very important in the study of chemistry, especially in the oxidation reduction reaction material. STAD learning model with problem posing strategy. This study aims to train students' creative thinking skills through the application of Student Teams Achievement Divisions (STAD) cooperative learning models with problem posing strategies in the oxidation-reduction reaction material. The Study used one group pretest posttest design in X MIA class MA Kanjeng Sepuh Sidayu Gresik with a total of 51 students conducted during two meetings. The results of the data obtained were analyzed using quantitative analysis and The result of this research are the students' creative thinking skills have increased, this is reinforced by the N-gain score obtained by students. Students' creative thinking skills in the oxidation reduction reaction material increase in each indicator, and student learning outcomes have an average score in class X MIA of 89.41%. Classical completeness learning outcomes of class X MIA students is 90.19%. That is to say that students who followed the learning process have complete learning outcomes .